Density-Dependent Birth and Death Processes with Controlled Immigration - KUMAR, Krisna (Institutional Knowledge at Singapore Management University, 1993)
A density-dependent birth and death process in which immigration is permitted only when the number of particles in the system is less than a positive integer kis considered. An explicit expression for the probability generating function of the population size is obtained by using a direct and unconventional approach. Special cases are discussed.